This question can be solved by using kinetic-potential energy postulate. It states that for any point sum of potential and kinetic energy of a body is same.
[tex] E_{sum} = E_{kinetic}+ E_{potential}[/tex]
At the given height potential energy is:
[tex]E_{potential} =m*g*h \\ E_{potential} =0.70*3.35*9.81 \\ E_{potential} =23J[/tex]
When the body reaches ground height is 0m and the potential energy is 0J. This means that all potential energy is transformed into kinetic energy.
[tex]E_{kinetic} =23J[/tex]
At the moment when body hits the ground the kinetic energy is 23J.